Cystic echinococcosis in South America: systematic review of species and genotypes of Echinococcus granulosus sensu lato in humans and natural domestic hosts - Cucher, Marcela Alejandra (2015)
OBJECTIVE:To systematically review publications on Echinococcus granulosus sensu lato species/genotypes reported in domestic intermediate and definitive hosts in South America and in human cases worldwide, taking into account those articles where DNA sequencing was performed; and to analyse the density of each type of livestock that can act as intermediate host, and features of medical importance such as cyst organ location.METHODS:Literature search in numerous databases. We included only articles where samples were genotyped by sequencing since to date it is the most accurate method to unambiguously identify all E. granulosus s. l. genotypes. Also, we report new E. granulosus s. l. samples from Argentina and Uruguay analysed by sequencing of cox1 gene.RESULTS:In South America five countries have cystic echinococcosis cases for which sequencing data are available: Argentina, Brazil, Chile, Peru and Uruguay, adding up 1534 cases. E. granulosus s. s. (G1) accounts for most of the global burden of human and livestock cases. Also E. canadensis (G6) plays a significant role in human cystic echinococcosis. Likewise, worldwide analysis of human cases showed that 72.9% are caused by E. granulosus s. s. (G1) and 12.2% and 9.6% by E. canadensis G6 and G7, respectively.CONCLUSIONS:E. granulosus s. s. (G1) accounts for most of the global burden followed by E. canadensis (G6 and G7) in South America and worldwide. This information should be taken into account to suit local cystic echinococcosis control and prevention programmes according to each molecular epidemiological situation. This article is protected by copyright. All rights reserved.